Skeletal overgrowth in transgenic mice that overexpress brain natriuretic peptide - Suda, Michio (The National Academy of Sciences, 1998)
Longitudinal bone growth is determined by the process of endochondral ossification in the cartilaginous growth plate, which is located at both ends of vertebrae and long bones and involves many systemic hormones and local regulators. Natriuretic peptides organize a family of three structurally related peptides: atrial natriuretic peptide, brain natriuretic peptide (BNP), and C-type natriuretic peptide. Atrial natriuretic peptide and BNP are cardiac hormones that are produced predominantly by the atrium and ventricle, respectively. C-type natriuretic peptide occurs in a wide variety of tissues, where it acts as a local regulator. These peptides can influence body fluid homeostasis and blood pressure control through the activation of two guanylyl cyclase (GC)-coupled natriuretic peptide receptor subtypes—GC-A and GC-B. We report here marked skeletal overgrowth in transgenic mice that overexpress BNP. Transgenic mice with elevated plasma BNP concentrations exhibited deformed bony skeletons characterized by kyphosis, elongated limbs and paws, and crooked tails. Bone abnormalities resulted from a high turnover of endochondral ossification accompanied by overgrowth of the growth plate. Studies using an in vitro organ culture of embryonic mouse tibias revealed that BNP increases the height of cartilaginous primordium directly, thereby stimulating the total longitudinal bone growth. The present study demonstrates that natriuretic peptides can affect the process of endochondral ossification.